2017
DOI: 10.1515/znc-2017-0015
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the route to cyclic monoterpenes in Chrysomelina leaf beetles: source of new biocatalysts for industrial application?

Abstract: Abstract:The drastic growth of the population on our planet requires the efficient and sustainable use of our natural resources. Enzymes are indispensable tools for a wide range of industries producing food, pharmaceuticals, pesticides, or biofuels. Because insects constitute one of the most species-rich classes of organisms colonizing almost every ecological niche on earth, they have developed extraordinary metabolic abilities to survive in various and sometimes extreme habitats. Despite this metabolic divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 125 publications
0
9
0
Order By: Relevance
“…4 ), thereby changing the stereochemistry of hydride addition to generate the R stereocenter. The newly discovered R -selective cyclization by AmISY may offer valuable biocatalytic access to a larger range of poorly accessible iridodial- and nepetalactol-related synthons ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…4 ), thereby changing the stereochemistry of hydride addition to generate the R stereocenter. The newly discovered R -selective cyclization by AmISY may offer valuable biocatalytic access to a larger range of poorly accessible iridodial- and nepetalactol-related synthons ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…In insects, terpenes play essential roles as sex pheromones, trail pheromones, and aggregation and alarm pheromones, as well as in the defense against pathogens [26,27]. It has been postulated that insects can synthesize them de novo, generally as monoterpenes, and they also have the ability to sequester terpenes produced by host plants or endosymbiotic microorganisms [26][27][28]. Monoterpenes are presumably assembled from isopentenyl diphosphate (IDP) and dimethylallyl diphosphate (DMADP) derived from the mevalonate route.…”
Section: Discussionmentioning
confidence: 99%
“…Monoterpenes are presumably assembled from isopentenyl diphosphate (IDP) and dimethylallyl diphosphate (DMADP) derived from the mevalonate route. In this metabolic pathway, the transor cisisoprenyl diphosphate synthases (IDSs) catalyze the condensation of IDP with one or two isomers of DMADP [26][27][28][29][30]. Trans-IDS enzymes have the particularity of being able to catalyze the syntheses of both precursors and final metabolites, and they can also produce monoterpenes and sesquiterpenes, depending on the cofactor to which they are exposed [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Biosynthetic insights have been obtained from studies on larvae of chrysomelid leaf beetles, which accumulate the iridoid-related monocyclic dialdehydes chrysomelidial and plagiodial (11). Feeding experiments with isotopically-labeled precursors and the discovery of some of the enzymes involved in chrysomelidial formation demonstrated that leaf beetles produce these compounds by a series of chemical reactions similar to those that occur in plants (12)(13)(14)(15). Although the enzymatic basis for this pathway has not been completely established, the fact that the known enzymes are unrelated to their counterparts in plants suggests independent evolution of the pathway occurred (14).…”
Section: Introductionmentioning
confidence: 99%